An Anionic β‐Diketiminato Oxoborane with a B–O Double Bond. Issue 21 (6th May 2019) - Liu, Jingjing; Yu, Jiaxiu; Meng, Yinfeng; Jin, Lijie; Sun, Wei; Hou, Lei; Chen, Sanping; Zeng, Fanlong; Li, Anyang; Wang, Wenyuan
Abstract : A rigid β‐diketiminate ligand was used to synthesize a cationic hydroxyborane and an anionic oxoborane. The anionic oxoborane has a negatively charged oxo‐group, which possesses a 1.301(3) Å B–O double bond and interacts with the hydrogen bond of an imidazolium cation. Theoretical calculations successfully illustrate the unsaturated nature of the B–O bond and the stability of the conjugated C3 N2 B‐ring in the oxoborane. The isolation of the new oxoborane compound offers promising approaches to unsaturated boron species. Abstract : An anionic oxoborane 3 was synthesized by deprotonation of cationic hydroxyborane 2 with a rigid β‐diketiminate ligand employing an N‐heterocyclic carbene as strong base. Molecule 3 has a negatively charged oxo‐group with a 1.301(3) Å B–O bond, which reveals B–O double bond character. Theoretical calculations explain the unsaturated nature of the B–O bond and the stability of the oxoborane anion.